Ingles Jurídico - DE325 - 202102 - Gordillo Zlosilo, Mare Duvbranka (2021)
English has become the universal language for business and all related subjects making it imperative for students to read, write, speak and be exposed to the language through their academic studies, research, work and any other activity related to the development of their profession. Therefore, this elective course has been designed and is aimed at involving students in topics related to legal issues in which they will be able to read, comprehend and produce oral and written pieces of work based on the information provided as well as their knowledge. The course will provide students the opportunity to review information and their understanding of legal matters within the common law system. Students will also be required to express themselves both orally and in writing using a diversity of techniques that will allow them to organize their speeches or texts correctly and naturally. For these purposes, students will need to familiarize themselves with all relevant vocabulary and legal jargon.